Assessment of cone survival in response to CNTF, GDNF, and VEGF165b in a novel ex vivo model of end-stage retinitis pigmentosa. - Lipinski, D; Singh, MS; Maclaren, R (2011)
PURPOSE: To develop a robust ex vivo model for evaluating cone survival in end-stage retinitis pigmentosa (RP) and apply this to quantify the effects of putative neuroprotective compounds. METHODS: Rhodopsin knockout mice were crossed with OPN1-GFP reporter mice so that GFP-positive cones could be identified against the background of a rod-specific degeneration. Retinal explants were harvested from 10-week-old mice and maintained in organotypic culture. Ciliary neurotrophic factor (CNTF), glial cell-derived neurotrophic factor (GDNF), or vascular endothelial growth factor 165b (VEGF(165b)) was administered daily to treatment groups at three doses (200 ng/mL, 100 ng/mL, or 50 ng/mL; n = 5 explants per group). Fluorescence microscopy was performed on days 1, 3, 5, 7, 9, and 12 to document the number of GFP-expressing cones. RESULTS: Cone survival could be assessed reliably and reproducibly in this model, and cone degeneration was significantly greater in the absence of rods, in keeping with clinical observations of RP. Daily administration of 200 ng/mL CNTF led to significantly increased cone survival compared with sham-treated controls. The effect was dose dependent; 100 ng/mL CNTF reduced cone loss but to a lesser extent, and 200 ng/mL GDNF showed significant protection against cone loss at later time points (day 9-12) but was much less effective than CNTF at all doses. VEGF(165b) showed no neuroprotective effect in this model at any dose. CONCLUSIONS: This model allows precise quantification of the neuroprotective effects of various compounds on cone survival and may therefore provide a robust method of screening neuroprotective compounds before application in vivo.